Distribution of towns, cities and infrastructure in Holland's Noorderkwartier up to around 1700 (OverHolland, 2013)
The first printed map of the Zuiderzee and the marked navigation channels in the western part of the Wadden Sea was produced by Lucas Jans-zoon Waghenaer in 1584. It differs from nautical charts of the area published later in that  it also shows the inland waterways of Holland’s Noorderkwartier (‘Northern Quarter’). The map provides a rare picture of the infrastructure and the distribution pattern of towns and cities in the area in the late sixteenth century. Land reclama-tion would alter the map dramatically in the centuries that followed, but waterways remained the chief means of transporting both people and goods right up to the midnineteenth century. This only changed with the advent of the railways.The exact area covered by the term Noorderkwartier is a matter of debate. In this article it is used to mean the whole area north of the North Sea Canal, including West Friesland. A study of railway station sites in the area on behalf of the Province of North Holland was completed by the ‘Mapping Randstad Holland’ research group in December 2011. The main components of the current railway network in the Noorderkwartier – the railway lines and most of the station sites – are already more than a century old. This outline of the topographical development of the area reveals the distribution pattern  of towns and cities onto which the network was grafted. In addition, the numerous historical studies of the area clearly show the exceptional relationship between the geographical, socioeconomic and political/administrative factors that determined the development of the Noorderkwartier. Consultation of this extensive literature has thus yielded insights of great relevance to our research into the Randstad.